2017
DOI: 10.1136/medethics-2016-103930
|View full text |Cite
|
Sign up to set email alerts
|

The role of religious beliefs in ethics committee consultations for conflict over life-sustaining treatment

Abstract: Previous research has suggested that individuals who identify as being more religious request more aggressive medical treatment at end of life. These requests may generate disagreement over life-sustaining treatment (LST). Outside of anecdotal observation, however, the actual role of religion in conflict over LST has been underexplored. Because ethics committees are often consulted to help mediate these conflicts, the ethics consultation experience provides a unique context in which to investigate this questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…(1,2) Religion has been found to be central to conflict over life sustaining treatment decisions in about 25% of cases and often involves family requests for life sustaining treatments on the basis of miracles or other religious beliefs. (3)(4)(5)(6) Although surrogates often rely on faith to make decisions and cope (7)(8)(9)(10) there is evidence that clinicians do not discuss religious beliefs in family meetings, even when they are an important concern of the family. (11) Although prior research on patients making their own decisions has found that more religious patients tend to prefer and receive more life sustaining treatments at the end of life than those who are less religious, (12)(13)(14) there is very little research describing the role that religion and spirituality play in surrogate decision making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1,2) Religion has been found to be central to conflict over life sustaining treatment decisions in about 25% of cases and often involves family requests for life sustaining treatments on the basis of miracles or other religious beliefs. (3)(4)(5)(6) Although surrogates often rely on faith to make decisions and cope (7)(8)(9)(10) there is evidence that clinicians do not discuss religious beliefs in family meetings, even when they are an important concern of the family. (11) Although prior research on patients making their own decisions has found that more religious patients tend to prefer and receive more life sustaining treatments at the end of life than those who are less religious, (12)(13)(14) there is very little research describing the role that religion and spirituality play in surrogate decision making.…”
Section: Introductionmentioning
confidence: 99%
“…This may be positive, such as feeling comforted by prayer, or negative, such as feelings that a negative event is a punishment for past wrongdoing or sin. (18) Finally, because of evidence that belief in miracles often arises in end of life decision making, (3,5) we addressed this dimension of belief.…”
Section: Introductionmentioning
confidence: 99%
“…One source of ethical challenge may relate to differing valuations of life between patients/families and their treating physicians on account of religion. Indeed, religious values impact some patient (and family) treatment decisions strongly, [1][2][3][4][5] and similarly, the attitudes of religious physicians toward end-of-life care treatment decisions can differ substantially from their nonreligious colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…Initial evidence suggests such integration may result in pro-active involvement in supporting gravely ill patients and their family surrogates and assisting them in coming to terms with their condition and making difficult treatment decisions. 20,22,23,38 In a prior report, when we examined the chaplains’ descriptions of their care we found evidence for a low level of pro-active integration. 33 Only 15% of the care provided by the chaplains had any focus on decision-making and less than 5% described involvement in family meetings.…”
Section: Discussionmentioning
confidence: 80%